The Euphorbia bivonae aggregate (Euphorbiaceae) in the Central Mediterranean area: First report of Euphorbia papillaris from Tunisia - Mokni, Ridha El; Barone, Giulio; Domina, Gianniantonio (Phytotaxa, 2024)
During floristic field exploration within the Tunisian territory, an interesting Euphorbia population was sampled from the Haouaria region in Cap-Bon peninsula. After critical study of the collected specimens against closely related taxa of the Euphorbia bivonae aggregate and following review of relevant literature and herbarium specimens, that population was identified as E. papillaris. This species is very rare and was considered endemic to western Sicily. The revision of historical herbarium specimens in the main European herbaria led to document the occurrence of this species also in Libya. An updated geographical distribution for the E. bivonae aggregate in the Central Mediterranean area as well as floristic and ecological data are here provided. An identification key is also presented.